Insight into the Mechanism of CO Oxidation on WO3(001) Surfaces for Gas Sensing: A DFT Study - Hua Jin; Hegen Zhou; Yongfan Zhang (Sensors, 2017)
The mechanism of CO oxidation on the WO3(001) surface for gas sensing performance has been systematically investigated by means of first principles density functional theory (DFT) calculations. Our results show that the oxidation of CO molecule on the perfect WO3(001) surface induces the formation of surface oxygen vacancies, which results in an increase of the surface conductance. This defective WO3(001) surface can be re-oxidized by the O2 molecules in the atmosphere. During this step, the active O2− species is generated, accompanied with the obvious charge transfer from the surface to O2 molecule, and correspondingly, the surface conductivity is reduced. The O2− species tends to take part in the subsequent reaction with the CO molecule, and after releasing CO2 molecule, the perfect WO3(001) surface is finally reproduced. The activation energy barriers and the reaction energies associated with above surface reactions are determined, and from the kinetics viewpoint, the oxidation of CO molecule on the perfect WO3(001) surface is the rate-limiting step with an activation barrier of about 0.91 eV.